NILAI EKONOMI PEMANFAATAN WADUK SUNGAI PAKU UNTUK KEGIATAN BUDIDAYA PERIKANAN DI KECAMATAN KAMPAR KIRI KABUPATEN KAMPAR - ummiati Sri; Eriyati Eriyati; Aulia Fahda Ando (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
Sungai Paku Reservoir is a reservoir located in Sungai Paku Village, Kampar Kiri District, Kampar Regency. This reservoir is used for various needs, including for irrigation, tourism objects, fisheries activities, both capture fisheries and aquaculture using the floating net cage system (KJA) or the ground pond system. Utilization of the Paku River Reservoir has not been measured economically, so it is necessary to conduct a study on the economic value of the use of the reservoir. This study aims to calculate the total economic value of the use of the reservoir for floating net cages and ground ponds. The method used is the market price method.The results showed that the total economic value of the use of the Paku River Reservoir for the benefit of fishery activities was Rp. 3,670,637,000,- year, which consists of on the utilization of floating net cage fish cultivation (KJA) of Rp. 957,296,000, /year and a land pool of Rp. 2,713,341,000 /yearKeyword: Economic Value, Benefits of Reservoirs, Floating Net Cages, Ground Pool